Herramienta interactiva para influenciar hábitos de compra alimenticia saludables en los consumidores de tiendas de barrio de la ciudad de Medellín (2019)
This Project talks about the study and analysis of the customs and food consumption habits of a population with a nutritional lack of knowledge and how this affect their day-to-day purchase decisions in the closest neighborhood stores. One of the main factors involved in the development of this problem is the lack of knowledge about what it is and what it takes to have a balanced diet according to the available budget (A. Hernández, 2000) for that reason it is necessary to consider taking this knowledge to the homes with the purpose of raising awareness about which are the strategies, to implement, in ale to potentiate a more balanced food intake (Ministerio de Educación, 2016). Taking into account the above, it is questioned how from the interaction with a communicative element prior to the time of purchase, it is possible to transmit this knowledge, with the aim of improving the ways of feeding, influencing food buying habits in a healthier way, considering the purchase interaction and the exchange of nutritional knowledge, with the idea of influencing the decision making of these consumers and encouraging a conscious food purchase. The design response interactively intervenes at the moment of the food purchase, offering the possibility of evaluating the nutritional contribution values from the products thought to acquire, focusing specifically on the breakfast time, due to the level of relevance that this food has in the caloric, energetic and nutritional contribution of the whole day, in addition that the customs and alimentary preferences of the population indicate a repetitive pattern of consumption of the same products that make up the breakfast in the hour of the night